Aqueous extracts of Physalis peruviana L. fruit promote apoptosis by overexpression of caspases 9/3 and balancing the redox profile of cutaneous melanoma cells - da Silva A.P. (2024)
© 2024 SAABPhysalis peruviana L. (PP), commonly known as golden berry, is a fruit renowned for its nutritional and medicinal properties. This study explores the antineoplastic potential of PP fruit extracts at varying stages of maturation, focusing on their impact on cutaneous melanoma cells. We analysed aqueous extracts from PP fruits at three distinct ripening phases, emphasizing their phenolic composition and antioxidant properties. Our in vitro assessments reveal that these extracts not only induce apoptosis in melanoma cells but also significantly upregulate caspase 9 and caspase 3 expression, leading to reduced cell viability. Moreover, the extracts inhibit melanoma cell migration and effectively modulate redox balance, suggesting an intricate interplay with cellular oxidative processes. These findings highlight the potential of PP fruit extracts as adjuvant agents in melanoma treatment or as a foundation for novel anticancer drug development, targeting specific pathways in cutaneous melanoma. Given these promising results, we advocate for subsequent in vivo studies and clinical trials to further elucidate the therapeutic efficacy and mechanisms of these PP extracts, thereby advancing future cancer therapeutic strategies.